DIFUSION DE NOTICIAS FALSAS EN REDES SOCIALES Y SU IMPACTO EN LA PERCEPCIÓN DE LOS ESTUDIANTES DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO EXTENSIÓN QUEVEDO., AÑO 2024. - Suàrez Miranda, Bryan Josuè (2024)
This phenomenon distorts reality and puts students' academic and social education at risk. Therefore, the study focuses on identifying sources of fake news, evaluating the credibility that students give to information on social networks and analyzing their impact. Understanding this problem is essential to design educational strategies that strengthen critical thinking and media literacy in future generations. This context underlines the need to analyze the impact of fake news on students' academic and social education, as well as to implement strategies that promote critical thinking and responsible management of information. Although there are studies on fake news, few focus on specific contexts such as Quevedo, offering a novel perspective on how local factors influence the perception of information. This project will also provide useful empirical data and concrete recommendations to strengthen students' media education, helping them to critically navigate digital environments. This research is classified as descriptive and correlational, as it seeks to characterize the phenomenon of the spread of fake news and establish significant relationships between exposure to these news and students' perceptions. The approach will allow for the identification of patterns and connections that explain their impact on the formation of opinions and beliefs. The use of a mixed methodology responds to the complexity of the problem, providing both depth in the analysis of individual experiences and breadth in the identification of generalizable trends.